Determinan Produk Domestik Regional Bruto Antar Kabupaten/Kota Di Daerah Istimewa Yogyakarta Tahun 2011-2020 - Arum Sari, Dyah; Sodik, Jamzani; Rahayu, Astuti (CV. Lafadz Jaya, 2022)
This study aims to determine the effect of Regional Original Income, General Allocation Funds, Special Allocation Funds, Revenue Sharing Funds on gross Regional Domestic Product in the Province of the Special Region of Yogyakarta in 2011-2020. Methods: this research uses quantitative methods. The type of data used in this study is secondary data with panel data cross section 5 districts/cities. The sample in this study is data from the APBD and GRDP according to the field of business at constant prices. The analytical tool in this study using software using Eviews 9. This study used the dependent variable and the independent variable. The dependent variable in this study is economic growth and the independent variables in this study are Regional Original Income, General Allocation Funds, Special Allocation Funds, Profit Sharing Funds. Hypothesis testing in this study using multiple linear regression. Results: The results of this study indicate that Local Original Income has a positive effect on Gross Regional Domestic Product, General Allocation Funds have a positive effect on Gross Regional Domestic Product, Special Allocation Funds have a positive effect on Gross Regional Domestic Product, Revenue Sharing Funds have no effect on Gross Regional Domestic Product.